Tantangan dan Solusi Penyalahgunaan Zat dari Perspektif Sosial di Masyarakat - ., HABIBULLAH (Maliki Interdisciplinary Journal, 2025)
Substance abuse is a complex global problem with serious implications for public health and social cohesion. This study examines the challenges of substance abuse from a social perspective in Indonesian society and identifies effective community-based solutions to address it. Using a qualitative research method with a phenomenological approach, this study involved in-depth interviews with 30 informants consisting of former substance users, social workers, community leaders, and health professionals. The results showed that the determinants of substance abuse include peer pressure, family dysfunction, socioeconomic disparities, and accessibility of substances. Social stigma was identified as a significant barrier to recovery and social reintegration. This study proposes several strategic solutions including: (1) community-based prevention programs by strengthening family institutions; (2) a harm reduction approach that is sensitive to the local cultural context; (3) post-rehabilitation social support networks; and (4) destigmatization through community education. This study contributes to the development of policies that integrate health, social, and law enforcement aspects by positioning substance users as individuals in need of help, not simply criminals. The findings of the study emphasize the importance of a collaborative and evidence-based approach that considers the social dynamics of the community in addressing substance abuse problems.